Cardiac MRI-Derived Right Ventricular Strain for Risk Stratification in Pediatric and Adolescent Arrhythmogenic Cardiomyopathy: A Multicenter Cohort Study. - Xu,W; Sa,F; Song,Y; Yang,S; Dong,Z; Chen,X; Tang,Y; Aisikaier,K; Ma,X; Jia,X; Zhou,P; Li,B; et al. (JACC Cardiovasc Imaging, 2026)
BACKGROUND: Pediatric and adolescent arrhythmogenic cardiomyopathy (ACM) is a clinically severe phenotype that remains underrepresented in cardiac magnetic resonance (CMR) research. The prognostic value of CMR-derived right ventricular deformation analysis in this population is unclear. OBJECTIVES: This study sought to describe the burden of severe cardiac outcomes in pediatric and adolescent ACM, and to assess the prognostic and incremental value of CMR-derived right ventricular global longitudinal strain (RVGLS) for risk stratification when incorporated into conventional clinical and CMR markers. METHODS: This multicenter study included consecutive pediatric and adolescent patients (aged ≤21 years) with ACM who underwent baseline CMR evaluation. We assessed clinical, electrocardiographic, and CMR parameters according to the 2010 Task Force Criteria, along with biventricular strain parameters. Severe cardiac outcomes were defined as a composite of malignant ventricular arrhythmias (MVAs), heart transplantation, and heart failure-related death. RESULTS: The cohort included 102 patients (16.3 ± 3.4 years; 72% male) and 95 controls (mean age: 15.6 ± 3.3 years; 70% male). During a median of 58-month follow-up, 51 (50%) patients experienced severe cardiac outcomes and 28 (27.5%) MVA outcomes. Reduced RVGLS was independently associated with severe cardiac outcomes (HR: 1.14; P = 0.004) and MVA outcomes (subdistribution HR: 1.15; P < 0.001) after adjustment for clinical and conventional CMR parameters. Incorporation of RVGLS significantly improved prediction of severe cardiac outcomes beyond both right ventricular-based and left ventricular-based multivariable models, with significant improvement in discrimination and reclassification. Kaplan-Meier analysis further showed that RVGLS ≥-12.2% identified patients at higher risk of severe cardiac outcomes and MVA outcomes (both log-rank P < 0.001). CONCLUSIONS: Pediatric and adolescent ACM manifests